Xenobiotic efflux pumps in isolated fish brain capillaries - Miller, David S.; Graeff, Claudia; Fricker, Stefanie; Fricker, Gert (American journal of physiology. Regulatory, integrative and comparative physiology, 2002)
To identify specific transporters that drive xenobiotics from the central nervous system to blood, the accumulation of fluorescent drugs was studied in isolated capillaries from killifish and dogfish shark brain using confocal microscopy and quantitative image analysis. In killifish brain capillaries, luminal accumulation of fluorescent derivatives of cyclosporin A and verapamil was concentrative, specific, and energy dependent (inhibition by KCN). Transport was reduced by PSC-833, but not by leukotriene C4, indicating the involvement of P-glycoprotein. The ability of capillaries to transport the cyclosporin A derivative was unchanged over 20 h, demonstrating the long-term viability of the preparation. Luminal accumulation of the fluorescent organic anions sulforhodamine 101 and fluorescein-methotrexate was also concentrative, specific, and energy dependent. Transport of these compounds was reduced by leukotriene C4, but not by PSC-833, indicating the involvement of a multidrug resistance-associated protein (Mrp). Similar results were obtained for isolated capillaries from dogfish shark. Immunostaining localized P-glycoprotein and Mrp2 to the luminal surface of the killifish brain capillary endothelium. These findings validate a new and long-lived comparative model for studying drug transport across the blood-brain barrier and, as in mammals, implicate P-glycoprotein and Mrp2 in transport from the central nervous system to blood in fish.
Gesehen am 25.04.2017